2002
DOI: 10.1017/s1355617702814370
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome for extended cold water drowning: A longitudinal case study

Abstract: There is little longitudinal data examining outcome of pediatric near-drowning. Most literature tracks status 5 years or less post insult, focusing primarily on gross neurologic status as opposed to more subtle neurocognitive deficits. The present case tracks the neuropsychological profile of a child who was submerged for 66 min, the longest time documented. Acute medical support was aggressive, and recovery was dramatic, being featured in multiple media reports. Although an article published 6 years after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Hypoxic brain injury is the major cause of morbidity after drowning incidents . In our study, neurologic sequelae after hospital discharge were evident in just one patient receiving only bystander CPR.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Hypoxic brain injury is the major cause of morbidity after drowning incidents . In our study, neurologic sequelae after hospital discharge were evident in just one patient receiving only bystander CPR.…”
Section: Discussionmentioning
confidence: 50%
“…Drowned children may indeed function at a level consistent with age expectations at discharge from the hospital. However, long‐term cognitive sequelae may not manifest until the child goes to school, and some defects such as executive dysfunction may not be detected until early adolescence . Long‐term follow‐up of drowned resuscitated children is therefore recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Although, in the original widely referred case report, the child was reported “recovering completely” [17,18]. Subsequent neuropsychological examination revealed impairment of visual-spatial abilities, mild dyslexic characteristics, dramatic memory impairment, full scale IQ of 85, impulsivity, poorconcentration and difficulty in sequential planning and organization.…”
Section: Methodsmentioning
confidence: 99%
“…Problems in skills such as divided attention and executive functions after hypoxic brain injury cannot be exclusively ruled out before early adulthood [18]. It has also been reported that neonates who were resuscitated in the delivery room had an increased risk of a low IQ score at 8 years of age even when they had not developed symptoms of encephalopathy during the neonatal period [43].…”
Section: Methodsmentioning
confidence: 99%
“…Scoring systems emphasizing functional outcome should be used because recent reports demonstrate that abnormalities may exist in so-called neurologically normal survivors. 71 Much of the clinical literature on drowning has focused on predictors of outcome. Victim-related factors associated with increased risk of death or poor outcome include being male, being nonwhite (in the United States), having a seizure disorder, and use of alcohol.…”
Section: Outcomementioning
confidence: 99%